Aktywność zawodowa i jej bariery w opinii osób z chorobami reumatycznymi - Cekiera, Rafał (Górnośląskie Studia Socjologiczne. Seria Nowa, 2020)
The article discusses the level of professional activity of people with rheumatic diseases and attempts to identify the most important they encounter. The analyses are based on a survey encompassing 338 respondents. The survey was conducted as part of a research project carried out in 2017 dedicated to the socio-professional circumstances of patients dealing with rheumatic diseases. The article shows a point of view of the group of people with illness who experienced health problems and complications firsthand. However, this issue is important not only for them, but has broad social repercussions relating to the labour market and overall functioning of social policies.